How does income inequality affect cooperation and punishment in public good settings? - Sebastian Prediger (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In the frame of decentralization reforms in Namibia, local water point associations evolved that have to collect water fees from community members to cover maintenance costs. Enforcement, however, is weak and water point associations have to rely on moral pleas. As a consequence, several users refuse to pay. I test the impact of informal sanction mechanisms on cooperation among water point users in groups with equal and unequal incomes. Interestingly, and in contrast to the vast majority of related studies, cooperation does not increase under the threat of punishment, though the punishment option was frequently used. At individual level I show that while punishments do not affect cooperative behaviour, they provoke counter-punishment. This suggests that peer-sanctioning mechanisms as a means to enforce norm-compliance are not accepted among water point association members. Contribution levels were higher in heterogeneous groups compared with homogenous ones, and both pro-social and anti-social punishments occurred more frequently in homogenous groups. A comparison between different income types further reveals that the poor contribute larger shares of their income than those endowed with higher incomes and that they use punishment as frequently and as vehemently as the better-off, despite higher opportunity costs.
Keywords: 330; income heterogeneity; public goods experiment; peer punishment; anti-social punishment; Namibia; Wasserversorgung; Öffentliches Gut; Einkommensverteilung; Kooperation; Strafe; Soziale Gruppe; Feldforschung; Namibia